Electricity generating capacity and performance deterioration of a microbial fuel cell fed with beer brewery wastewater - Koroglu, Emre Oguz; Ozkaya, Bestamin; Denktas, Cenk; Cakmakci, Mehmet (SOC BIOSCIENCE BIOENGINEERING JAPAN, 2014)
This study focused on using beer brewery wastewater (BBW) to evaluate membrane concentrate disposal and production of electricity in microbial fuel cells. In the membrane treatment of BBW, the membrane permeate concentration was 570 +/- 30 mg/L corresponding to a chemical oxygen demand (COD) removal efficiency of 75 +/- 5%, and the flux values changed between 160 and 40 L/m(2)-h for all membrane runs. For electricity production from membrane concentrate, the highest current density in the microbial fuel cell (MFC) was observed to be 1950 mA/m(2) according to electrode surface area with 36% COD removal efficiency and 2.48% CE with 60% BBW membrane concentrate. The morphologies of the cation exchange membrane and the MFC deterioration were studied using a scanning electron microscope (SEM), attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy, differential scanning calorimetry (DSC), and thermal gravimetric analysis (TGA). A decrease in the thermal stability of the sulfonate (-SO3H) groups was demonstrated and morphological changes were detected in the SEM analysis. (C) 2014, The Society for Biotechnology, Japan. All rights reserved.
Keywords: Microbial fuel cell; Membrane concentrate; Wastewater treatment; Membrane morphology; Thermal stability; CATION-EXCHANGE MEMBRANES; COMPOSITE MEMBRANES; NAFION MEMBRANE; FTIR; Biotechnology & Applied Microbiology; Food Science & Technology